PREDIKSI PERGESERAN PANGSA PASAR PADA BEBERAPA PRODUK ASURANSI KENDARAAN BERMOTOR MENGGUNAKAN PENDEKATAN RANTAI MARKOV - Panjaitan, Marta; Haryanto, Dwi; M. Nasyubun (Premium Insurance Business Journal, 2021)
The diversity of motor vehicle insurance products sold at PT Asuransi Central Asia cabang Cikini makes the choice of products can be tailored to the needs of each insurance buyer. This difference in needs is of course an important thing to be considered by the company in preparing a work plan in the future. By knowing market share and future market share changes, companies can more easily recognize the buying interest and selling power of the products they have. Market share and market share shifts between products in the future can be predicted using the Markov chain method. The result obtained is that insurance companies need to pay more attention to products that are still less desirable judging by the number of sales in a year. This aims to maintain the stability of product sales, especially the company's superior products to be more competitive when juxtaposed with conventional products sold also in other insurance companies.